Key outcome summaries of the scientific programme of the IRPA15 congress. (10th November 2021) - Weiss, Wolfgang; Salomaa, Sisko; Giorgio, Marina Di; Boyd, Mike; Thurston, Jim; Takala, John; Tokonami, Shinji; Vaillant, Ludovic; Coates, Roger; Kim, Jong Kyung
Abstract: This special issue of JRP includes a selection of research papers and review articles presented at the 15th Congress of the International Radiation Protection Association (IRPA15) as chosen by the scientific committee. All invited journal contributions are suitably expanded beyond the initial conference presentations to meet the criteria for a full journal article and include (a) presentation within a comprehensive radiological protection context and (b) additional data/interpretation. Published contributions address a wide spectrum of scientific topics and concepts to further develop the radiation protection (RP) system. They are based on scientific evidence and available experience in a wide spectrum of applications of the protection system. The IRPA is the international voice of the RP profession. It promotes excellence in RP by providing benchmarks of good practice, enhancing professional competence, and encourages the application of the highest standards of professional conduct, skills and knowledge for the benefit of individuals and society. Within the overarching theme of the conference 'Bridging RP Culture and Science—Widening Public Empathy' IRPA15 provided an invaluable opportunity to discuss and strengthen the relations between RP culture and science, and share developing scientific knowledge and related experience in RP among members of the scientific community, between representatives of key international organizations, including ICRP, IAEA, WHO, and NEA but also with the public. Some discussions focused on the rationale of available RP programmes and priorities, with an opportunity to identify and further develop key scientific issues of the current RP system as well as key processes for the interaction between members of the scientific community and society. The scientific programme of IRPA15 included eight topics and four thematic areas. The topical areas were: Underpinning Science; Dosimetry and Measurement; the System of Protection; Standards and Regulation; Practical Implementation—Medical Sector, as well as Industry and Research; Emergency Preparedness and Response; Existing Exposures and Non-ionizing Radiation. The thematic areas addressed were: Ethics; Communication and Public Understanding; RP Culture; Human Capital and Competency.